2021
DOI: 10.1016/j.cortex.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Ecological stress, amygdala reactivity, and internalizing symptoms in preadolescence: Is parenting a buffer?

Abstract: Ecological stress during adolescent development may increase the sensitivity to negative emotional processes that can contribute to the onset and progression of internalizing behaviors during preadolescence. Although a small number of studies have considered the link among the complex relations in ecological stress, amygdala reactivity and internalizing symptoms in childhood and adolescence, these studies have largely been small, cross-sectional, and often do not consider unique roles of parenting or sex. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 109 publications
1
13
0
Order By: Relevance
“…These decisions can be considered as ‘researcher degrees of freedom’ ( Simmons et al, 2011 ). While the decisions in Thijssen et al (2020) were consistent with the theory that motivated the study, other studies measuring environmental experiences in the ABCD study (as we, Demidenko et al (2021) , and others ( Gonzalez et al, 2020 ; Ip et al, 2022 ; Petrican et al, 2021 ; Taylor et al, 2020 ) have done may reasonably impose different decisions that may contribute to different results and conclusions. Thus, given the rich higher-order model in Thijssen et al (2020) , we first perform a replication of the original study using the full baseline data.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…These decisions can be considered as ‘researcher degrees of freedom’ ( Simmons et al, 2011 ). While the decisions in Thijssen et al (2020) were consistent with the theory that motivated the study, other studies measuring environmental experiences in the ABCD study (as we, Demidenko et al (2021) , and others ( Gonzalez et al, 2020 ; Ip et al, 2022 ; Petrican et al, 2021 ; Taylor et al, 2020 ) have done may reasonably impose different decisions that may contribute to different results and conclusions. Thus, given the rich higher-order model in Thijssen et al (2020) , we first perform a replication of the original study using the full baseline data.…”
Section: Introductionsupporting
confidence: 67%
“…To date, investigations using the ABCD study data have drawn upon different measures of the family environment and puberty when studying neurodevelopment. For instance, studies focused on neurodevelopment have used latent factors of the family environment ( Thijssen et al, 2020 , 2022 ), bio-psycho-social ecologies ( Gonzalez et al, 2020 ), neighborhood and family income/stress ( Demidenko et al, 2021 ; Ip et al, 2022 ; Sripada et al, 2021 ; Taylor et al, 2020 ) and material deprivation/threat/social support ( DeJoseph et al, 2022 ; Petrican et al, 2021 ), or individual scales of family-to-needs ratios ( Gonzalez et al, 2020 ; Rakesh et al, 2021), poverty levels ( Ellwood-Lowe et al, 2021 ), parental education ( Rakesh et al, 2021a , b ), area deprivation indices (Rakesh et al, 2021; Rakesh et al, 2021) and parental acceptance (Rakesh et al, 2021). As for measures of pubertal development (see reviews regarding measures and correspondence of pubertal scales: Cheng et al (2021) and Herting et al (2021) ), published works using ABCD data have used parent-reported pubertal development ( Demidenko et al, 2021 ; McNeilly et al, 2021 ; Thijssen et al, 2020 , 2022 ) or youth/parent reported averages of pubertal development ( Petrican et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent ABCD study similarly did not find a buffering effect of parental acceptance against ecological stress. Specifically, the interaction between ecological stress and parental acceptance was not significantly associated with amygdala reactivity during the emotional EN-back task ( Demidenko et al, 2021 ). It is possible that this specific index of caregiving (i.e., five items from the CRPBI) may not be capturing the more nuanced ways in which caregivers can protect against adversity, particularly with regard to the specific cortico-limbic connections considered in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The Culture and Environment working group (CE WG), described previously ( Zucker et al, 2018 ), is responsible for selecting measures and monitoring data pertaining to cultural factors and the social environment. To our knowledge, there are at least 17 published studies to date using CE measures, covering unique associations between family factors (e.g., conflict, monitoring, acceptance/warmth) and amygdala reactivity ( Demidenko et al, 2021 ); suicidality ( Janiri et al, 2020 ), maladaptive guilt ( Donohue et al, 2020 ), eating disorders ( Kerr et al, 2021 ), and early substance exposure ( Wang et al, 2021 ). In addition, school factors and prosocial behavior appear uniquely associated with general psychopathology, accounting for comorbidities across internalizing and externalizing behaviors ( Brislin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%